Transformational Leadership Behaviors of Unit Charge Nurses and the Motivation Status of Staff Nurses - Gülfigar Gülkaya; Sergül Duygulu (Association of Nurse Managers, 2020)
INTRODUCTION: The establishment of a safe and healthy work environment requires strong transformational nursing leadership and highly motivated nurses at all levels of the organization. This is especially important at the point of care or unit level where most front-line staff work, and patient care are delivered. This descriptive correlational study aimed to define transformational leadership behaviors of unit charge nurses and the motivation level of staff nurses working with them and the relationship between transformational leadership and motivation of nurses. METHODS: The study sample consisted of 108 unit charge nurses and 324 staff nurses. Data were collected using the Demographic Data Sheet, the Leadership Practices Inventory-the Self and Observer Form, the Social Desirability Scale, and the Job Motivation Scale. RESULTS: The average total score of the Leadership Practices Inventory of unit charge nurses was 129.11+-11.45 (min.: 30, max.: 150). Unit charge nurses stated that their most frequent leadership practice was 'encourage the heart' (27.27+-2.38). Their self-ratings on 'model the way' (p=0.000), 'challenge the process' (p=0.052), 'enable others to act' (p=0.000), and 'leadership practices' total scores (p=0.000) were statistically significantly higher than those of the staff nurses. Staff nurses' intrinsic motivation mean score was 41.43+-5.17 (min. point: 18, max: 54), extrinsic motivation mean score was 28.25+-4.31 (min.11, max: 33), and the total motivation mean score was 69.69+-8: 45 (min: 29, max: 87). A positive statistically significantly relationship was found between staff nurses' evaluation on unit charge nurses' total leadership practices and intrinsic (p=0.001), extrinsic (p=0.008) and total motivation mean scores (p=0.001). DISCUSSION AND CONCLUSION: The results of study showed that the motivation level of staff nurses was at a moderate level, yet we also found that unit charge nurses transformational leadership practices had a significant effect on staff nurses' motivation. Therefore, we have concluded that developing transformational leadership practices of unit charge nurses at healthcare institutions can increase the motivation of staff nurses.